Evaluation of the Efficacy of Antihelminthic Treatment with Oxantel-Pyrantel Pamoate and Reinfection by Geohelminths, in Children from two Populations in Sucre State - Denice Patete; Elvia Michelli; Marcos De Donato (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2005)
Efficacy of oxantel-pyrantel pamoate and helminthic reinfection were evaluated in children from both sexes between the ages of 3 and 14. We selected 289 children in total, 123 from Agua Blanca, Montes Municipality, and 166 from Malariologia, Cumana, Sucre Municipality. Feces samples were collected and freshly processed by a coproparasitologic analysis with saline solution and lugol, using also the methods of Ritchie, feces culture in agar plates, quantitative Kato-Katz and quantification of protozoan. Four post treatment samples were taken from each individual (weeks 1, 3, 5 and 10). The findings were presented in prevalencia charts; the tests of squared Ji (c2) and ANOVAmultiple, to 95% of dependability, were also applied, and classical methods were used to determine the efficacy and effectiveness of the drug, and helminthic reinfection. The prevalence of intestinal parasites was 99.19% for Agua Blanca and 85.54% for Malariologia. Trichuris trichiura was the most prevalent helminth in both populations (74.84% and 50.00%, respectively), and Blastocystis hominis was the most prevalent protozoan (73.17% and 40.96%, respectively). Most of the helminthic infections showed low levels and no statistically significant differences were seen between the populations (F=2,76; p>0,05 for Ascaris lumbricoides, F=2,13; p>0,05 for T. trichiura and F=1,17;p>0,05 for Necator americanus). Children between 7 and 10 years old were the most affected. Oxantel-pyrantel pamoate showed more efficacy and effectiveness towards A. lumbricoides than any other helminthic species. There were statistical differences in the reinfections between the two populations (C2=14,82; p>0,05). Environmental characteristics of each community could favor helminthic transmission and maintain the infection-reinfection cycle seen.